2015
DOI: 10.2527/jas.2014-8286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of added zinc in diets with ractopamine hydrochloride on growth performance, carcass characteristics, and ileal mucosal inflammation mRNA expression of finishing pigs1,2

Abstract: ABSTRACT:Two experiments were conducted to determine the effects of increasing the dietary Zn content on growth performance, carcass characteristics, plasma Zn, and ileal mucosal inflammation mRNA expression of finishing pigs fed diets containing ractopamine HCl (RAC; Elanco Animal Health, Greenfield, IN). In Exp. 1, 312 pigs (327 × 1050; PIC, Hendersonville, TN; 94 kg BW) were used in a 27-d study. There were 2 pigs per pen and 26 pens per treatment. Treatments included a corn-soybean meal diet (control; 0.66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
2
11
1
2
Order By: Relevance
“…No further evidence was reported in the literature regarding liver decrease when pigs were fed with RAC. However, similar to the observations of this study, RAC supplementation has been reported to increase liver yield (Paulk et al, 2015). More studies should be conducted to elucidate this fact.…”
Section: Organs and Testis Weight And Yieldsupporting
confidence: 64%
“…No further evidence was reported in the literature regarding liver decrease when pigs were fed with RAC. However, similar to the observations of this study, RAC supplementation has been reported to increase liver yield (Paulk et al, 2015). More studies should be conducted to elucidate this fact.…”
Section: Organs and Testis Weight And Yieldsupporting
confidence: 64%
“…Crome et al (1996) demonstrated that increasing the concentration of RAC in the diet resulted in a linear LEA increase and a linear decrease in first rib, 10th rib, and last lumbar backfat thicknesses. Paulk et al (2015) reported increases in HCW of 3% and a 6% increase of loin depth and a corresponding 16% decrease in backfat depth when pigs were exposed to the same RAC feeding regimen as the current study. Burnett et al (2016) showed that 10 mg/kg RAC tended to increase HCW by 3%, increased LEA by 10%, but only tended to decrease 10th and last rib backfat.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 77%
“…Carr et al (2005) reported that RAC-fed barrows had increases of 16% in ADG and 19% in G:F but no differences in ADFI. Using barrows and gilts raised at the same farm as the current study, Paulk et al (2015) reported RAC fed during the final 35 d of feeding increased ADG by 11%, reduced ADFI by 6%, and increased G:F by 17%. In contrast to these studies, Armstrong et al (2004) reported that RAC fed to barrows did not influence ADG or ADFI, and Stites et al (1991) showed that regardless of RAC level in the feed, ADFI was not affected.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 99%
“…Patience et al (2011), Rambo et al (2012), and Fry et al (2013 reported that an organic source of Zn improved performance over that of Zn from an inorganic source. Most recently, Paulk et al (2015) reported where Zn from ZnO linearly improved feed efficiency in one study but Zn from inorganic and organic sources had no response in the presence of ractopamine in a second study. Conversely, when Gowanlock et al (2013) fed diets without any trace mineral supplementation for the entire finishing period or supplemented just Zn from an organic source, no significant differences in growth performance (gain, feed intake, or feed efficiency) or in carcass characteristics (HCW, back fat depth, or loin muscle area) were observed due to a lack of Zn supplementation despite the inclusion of 10 mg/ kg ractopamine for 21 d prior to marketing.…”
Section: Continuedmentioning
confidence: 99%
“…Neither Zn nor RAC adversely affected antimicrobial resistance. However, extended feeding of 125 mg/kgtal Zn with ractopamine in the diet (Paulk et al, 2015). Copper also has been shown to improve growth and feed intake of finishing pigs (Coble et al, 2014).…”
mentioning
confidence: 99%